1985
DOI: 10.1128/iai.48.3.720-728.1985
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of human lysozyme, muramidase-inactive lysozyme, and cationic polypeptides against Streptococcus sanguis and Streptococcus faecalis: inhibition by chitin oligosaccharides

Abstract: The bisis of the bactericidal activity of human lysozyme against Streptococcus sanguis was studied. Experiments were designed to evaluate the role of lysozyme muramidase activity in its bactericidal potency. Inactivation of the muramidase activity of lysozyme was achieved by reduction of essential disulfides with dithiothreitol (DTT) or by incubation with the chitin oligosaccharides chitotriose and chitobiose. Muramidaseinactive lysozyme, prepared by reduction with DTT, was equal in bactericidal potency to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(95 citation statements)
references
References 50 publications
8
87
0
Order By: Relevance
“…Although the muramidase activity (cleaveage of the glycosidic bond between N-acetylmuramic acid and N-acetyl glucosamine in the bacterial peptidoglycan) of lysozyme has been implicated in its antibacterial activity (especially against Gram-positive bacteria), it has also been shown that the bactericidal potency of lysozyme is not only a result of muramidase activity but also of its cationic and hydrophobic properties [58,59]. Furthermore, it has been demonstrated that the bactericidal effect of lysozyme is synergistically enhanced with hBD-2 and hBD-3 [36,60].…”
Section: Elafinmentioning
confidence: 99%
“…Although the muramidase activity (cleaveage of the glycosidic bond between N-acetylmuramic acid and N-acetyl glucosamine in the bacterial peptidoglycan) of lysozyme has been implicated in its antibacterial activity (especially against Gram-positive bacteria), it has also been shown that the bactericidal potency of lysozyme is not only a result of muramidase activity but also of its cationic and hydrophobic properties [58,59]. Furthermore, it has been demonstrated that the bactericidal effect of lysozyme is synergistically enhanced with hBD-2 and hBD-3 [36,60].…”
Section: Elafinmentioning
confidence: 99%
“…Lysozyme is 14 kd enzyme directed against the ␤ 1 3 4 glycosidic bond between N-acetylglucosamine and N-acetylmuramic acid residues that make up peptidoglycan, the cell wall material that gives bacteria their shape. In addition to enzymatic lysis of bacterial cell walls, lysozyme can also kill bacteria by a nonenzymatic mechanism [22]. Although lysozyme is highly active against many Gram-positive species, for example, Bacillus megaterium, Micrococcus lysodeicticus, and many streptococci, it has been described as ineffective against Gram-negative bacteria [23] unless potentiated by certain cofactors (lactoferrin, antibody-complement or hydrogen peroxide-ascorbic acid).…”
Section: Activities Of Antimicrobial Polypeptides From Respiratory Sementioning
confidence: 99%
“…These disorders result in the loss of the "acquired pellicles" with a subsequent increase in the number and severity of microbial infections (11,32). These observations are supported by several reports suggesting that the salivary secretions play a role in modulating colonization by opportunistic pathogens (9,10,20) and resident oral fiora (3,8,27,34,42).…”
Section: Discussionmentioning
confidence: 61%
“…Salivary secretions may interfere with the adhesion of bacteria to oral surfaces to facilitate their clearance from the oral cavity (21,23,30,39,40). In addition, salivary secretions have been shown to contain substances with potential antimicrobial activity that directly affect the growth and viability of pathogenic organisms (8,13,27,35,36,39,41,42). However, the role of salivary secretions in modulation of viral infections in the oral cavity has received little attention.…”
mentioning
confidence: 99%